Expert’s technical review on 2D games with religious elements - Norkhairani, Abdul Rawi; Maizan, Mat Amin; Azilawati, Rozaimee (Science and Engineering Research Support Society, 2016)
Previously, we present the motivation for developing 2D game named My Journey to the Mosque (MJTM) that enables to teach children to recite zikir indirectly. There is a need for usability evaluation of the prototype before it can be tested against actual user. Therefore, in order to verify the prototype that has been developed, a usability study was conducted among technical experts. The experts were one from Islamic entertainment industry and two academicians from Multimedia School. A questionnaire has been developed to collect feedback from the expert reviewer. Among the aspects observed by the experts were contents, navigation or interactivity, presentation of the prototype and the use of animations. These are important aspects to be considered according to various previous studies. Results shown that most of the aspects observed by the reviewers were above the average score of 4.00 according to the Likert scale. Findings of this study will be used as a guideline for further enhancements of the prototype.